Feasibility and potential efficacy of commercial mHealth/eHealth tools for weight loss in African American breast cancer survivors: pilot randomized controlled trial. Issue 4 (9th December 2018) - Ferrante, Jeanne M; Devine, Katie A; Bator, Alicja; Rodgers, Ashley; Ohman-Strickland, Pamela A; Bandera, Elisa V; Hwang, Kevin O
Abstract : Publically available internet programs or cell phone apps, such as SparkPeople and Fitbit, show promise for weight loss in African American women with breast cancer. Abstract: Weight management after breast cancer (BC) treatment in African American (AA) women is crucial to reduce comorbid conditions and health disparities. We examined feasibility and potential efficacy of commercial eHealth/mHealth tools for weight management in AA BC survivors in New Jersey. Participants ( N = 35) were randomized to an intervention (SparkPeople) plus activity tracker, Fitbit Charge ( n = 18), or wait-list active control group (Fitbit only, n = 17). Anthropometric, behavioral, and quality of life (QOL) outcomes were collected at baseline, 3, 6, and 12 months. Differences in outcomes were assessed using intent-to-treat analysis. Retention was 97.1%. Both groups lost weight, with no significant differences between groups. At month 6, mean weight change was: intervention: −1.71 kg ( SD 2.33; p = .006), 33.3% lost ≥3% of baseline weight; control: −2.54 kg ( SD 4.00, p = .002), 23.5% lost ≥3% weight. Intervention participants achieved significant improvements in waist circumference (−3.56 cm, SD 4.70, p = .005), QOL ( p = .030), and use of strategies for healthy eating ( p = .025) and decreasing calories ( p < .001). Number of days logged food per week was associated with decreases in waist circumference at 6 months ( β −0.79, 95% CI, −1.49, −0.09, p = .030) and 12 months (β −2.16, 95% CI, −4.17, −0.15, p = .038). Weight loss was maintained at 12 months. This is the first study to demonstrate potential efficacy of commercial eHealth/mHealth tools for weight loss in AA BC survivors, without additional counseling from the research team. If effective, they may be convenient weight loss tools that can be easily and widely disseminated. Clinical Trials registration : ClinicalTrials.gov NCT02699983